2012
DOI: 10.1007/s00262-012-1361-y
|View full text |Cite
|
Sign up to set email alerts
|

Expression of monocyte chemoattractant protein-1 and CC chemokine receptor 2 in non-small cell lung cancer and its significance

Abstract: Expression of monocyte chemoattractant protein-1 (MCP-1) and CC chemokine receptor 2 (CCR2) and its significance has been demonstrated in some cancer cells in recent clinical studies. However, the role of tumor MCP-1 and CCR2 expression in non-small cell lung cancer (NSCLC) remains unknown. The aim of the present study was to investigate the prognostic significance of MCP-1 and CCR2 expression in NSCLC cells. The relationship between MCP-1 and CCR2 expression in NSCLC cancer cells was examined by immunohistoch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
31
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 40 publications
1
31
0
Order By: Relevance
“…Moreover, Zhang et al . reported that the presence of CCL2‐positive cancer cells was high in LUAD relative to LUSC and other histological types . A recent study demonstrated that Lewis lung carcinoma cells harbor the activating Kras G12C mutation, which upregulates CCL2 production linking cancer‐associated inflammation .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, Zhang et al . reported that the presence of CCL2‐positive cancer cells was high in LUAD relative to LUSC and other histological types . A recent study demonstrated that Lewis lung carcinoma cells harbor the activating Kras G12C mutation, which upregulates CCL2 production linking cancer‐associated inflammation .…”
Section: Discussionmentioning
confidence: 99%
“…34 Moreover, Zhang et al reported that the presence of CCL2-positive cancer cells was high in LUAD relative to LUSC and other histological types. 35 A recent study demonstrated that Lewis lung carcinoma cells harbor the activating Kras G12C mutation, which upregulates CCL2 production linking cancer-associated inflammation. 36 A previous study reported that knockdown of CCL2 and CCL4 in lung cancer cells could suppress macrophage invasion under co-culture conditions.…”
Section: Discussionmentioning
confidence: 99%
“…CCL2 binds to its receptor CCR2 to mediate its effect through an autocrine or paracrine manner (130). Expression of CCL2, CCR2 or in combination with IL6 and IL10 correlates with a worse prognosis in lung cancer patients (61,78,79). In various cancers, the crosstalk of TAMs with tumor cells via the CCL2/CCR2 axis play multiple roles in cancer development, such as monocyte/macrophage recruitment at the tumor site (131), tumor progression, EMT, invasion, and metastasis (132).…”
Section: Chemokines Ccl2mentioning
confidence: 99%
“…CCL2 is produced by endothelial cells and fibroblasts [12] and by a variety of activating cells, such as lymphocytes and macrophages [9]. Recent studies have reported that CCL2 is overexpressed in a majority of solid cancer types, including breast cancer, prostate cancer, esophageal carcinoma, colon cancer, pancreatic cancer, ovarian cancer [8, 13–17] and NSCLC [18]. …”
Section: Introductionmentioning
confidence: 99%
“…In patients with NSCLC, positive CCL2 expression was observed more frequently in men than in women, in never-smokers than in smokers, in adenocarcinoma than in other histological types, and in smaller tumors among the patients with NSCLC. However, there was no relationship of tumor CCR2 expression with gender, smoking habits, histologic type of tumor and tumor size [18, 24]. However, its roles in NSCLC development remain unclear.…”
Section: Introductionmentioning
confidence: 99%